Analysis of Learning Motivation in the Implementation of “Kurikulum Merdeka Belajar Paket C” at PKBM Azizi Medan - Tiurma Sitinjak (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to analyze the motivation to learn in implementing the “kurikulum merdeka belajar paket C” at PKBM Azizi Medan. This study used a qualitative approach with a descriptive method where the subjects in this study were PKBM Azizi Medan managers. Data collection was carried out by observation, interview and documentation methods. Based on the results of research at PKBM Azizi Medan, the application of learning motivation in implementing the independent learning curriculum at PKBM Azizi Medan, namely: 1) Giving freedom to citizens studying at PKBM Azizi in optimizing their talents; 2) Learning residents in PKBM are still adapting to the independent learning curriculum because learning residents are still experiencing culture shock with the continuing curriculum changes; 3) The learning motivation of learning residents begins to emerge from themselves since the implementation of the independent learning curriculum; 4) Lack of infrastructure to support learning motivation in the independent learning curriculum at PKBM Azizi.